Pharmacological evaluation of Euphorbia hirta, Fagonia indica and Capparis decidua in hypertension through in-vivo and in vitro-assays. Issue 10 (October 2021) - Ali, Muhammad Zeeshan; Mehmood, Malik Hassan; Saleem, Muhammad; Hamid Akash, Muhammad Sajid; Malik, Abdul
Abstract: Objective: This study determines the efficacy and probable underlying mode of action to the folk usage of Euphorbia hirta, Fagonia indica and Capparis decidua in hypertension. Methods: The aqueous-methanol extracts of E. hirta (EH.Cr), F. indica (FI.Cr) and C. decidua (CD.Cr) were tested for antihypertensive effects in rats using non-invasive and in-vasive blood pressure measuring apparatus. In-vitro assays were carried out using isolated rat aortae using PowerLab station. Results: EH.Cr, FI.Cr and CD.Cr at 500 mg/kg (orally) caused a fall in the mean systolic blood pressure in arsenic-induced hypertensive and normotensive rats, similar to nifedipine. In rat aortae, EH.Cr, CD.Cr and FI.Cr reversed low (20 mM), high (80 mM) K + and phenylephrine (P.E)-driven contractions, while F. indica partially inhibited high K + contractions. In the presence of TEA, F. indica remained unable to relax low K + contractions. EH.Cr and CD.Cr moved Ca ++ concentrations response curves to the right, like nifedipine. All fractions of EH.Cr and CD.Cr except aqueous, pet-ether and chloroform fractions of FI.Cr displayed Ca ++ antagonistic activity. FI.Cr, its ethyl acetate and aqueous fraction exhibited TEA-sensitive potassium channel activation. On baseline tension, test materials also produced phentolamine-sensitive vasospasm. Conclusion: E. hirta, F. indica and C. decidua possess antihypertensive activity in arsenic-induced hypertensive rats possibly mediated via endothelium-dependent vasorelaxation. In normotensive rats, E. hirta and C. decidua showed antihypertensive activities through endothelium-dependent and Ca ++ antagonistic pathways, while F. indica exhibited potassium channel activation and Ca ++ antagonistic like effects in its vasorelaxation. Additional weaker vasospastic effects were derived through α-adrenergic like pathways. Abstract : Euphorbia hirta, Fagonia indica, Capparis decidua, Antihypertensive, Ca ++ antagonist, Potassium channel activation.